The maize (Zea mays ssp. mays var. B73) genome encodes 33 members of the purple acid phosphatase family - González-Muñoz, Eliécer; Avendaño-Vázquez, Aida-Odette; Montes, Ricardo A. Chávez; de Folter, Stefan; Andrés-Hernández, Liliana; Abreu-Goodger, Cei; Sawers, Ruairidh J. H. (Frontiers in Plant Science, 2015)
Purple acid phosphatases (PAPs) play an important role in plant phosphorus nutrition, both by liberating phosphorus from organic sources in the soil and by modulating distribution within the plant throughout growth and development. Furthermore, members of the PAP protein family have been implicated in a broader role in plant mineral homeostasis, stress responses and development. We have identified 33 candidate PAP encoding gene models in the maize (Zea mays ssp. mays var. B73) reference genome. The maize Pap family includes a clear single-copy ortholog of the Arabidopsis gene AtPAP26, shown previously to encode both major intracellular and secreted acid phosphatase activities. Certain groups of PAPs present in Arabidopsis, however, are absent in maize, while the maize family contains a number of expansions, including a distinct radiation not present in Arabidopsis. Analysis of RNA-sequencing based transcriptome data revealed accumulation of maize Pap transcripts in multiple plant tissues at multiple stages of development, and increased accumulation of specific transcripts under low phosphorus availability. These data suggest the maize PAP family as a whole to have broad significance throughout the plant life cycle, while highlighting potential functional specialization of individual family members.